The Conceptualization of Emotions in German and Indonesian Idioms - Prita Azka Fatika; Ending Khoerudin; Nur Muthmainah (Journal of Education Research, 2026)
Idioms reflect how speakers conceptualize emotions through language and culture. This study aims to identify the conceptualization of emotions in German and Indonesian idioms and to examine the cultural influences underlying their similarities and differences, using a qualitative contrastive approach grounded in Lakoff and Johnson’s Conceptual Metaphor Theory to analyze idioms expressing anger, happiness, sadness, and fear. The findings reveal both direct and indirect conceptual equivalents. Direct conceptual equivalents indicate that many emotion idioms in both languages are shaped by shared embodied experiences, including bodily reactions, spatial orientation, and the heart as the seat of emotions. Meanwhile, indirect conceptual equivalents indicate that comparable emotions are often expressed through different metaphorical images shaped by cultural, historical, and environmental factors. Therefore, the conceptualization of emotions in German and Indonesian idioms shows the interaction between universal embodied cognition and culture-specific metaphorical elaboration.